Perancangan Multimedia Interaktif Percakapan Umum Tentang Traveling dalam Bahasa Korea sebagai Media Pembelajaran - yashinta puspita ayu (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2019)
Korea is currently forming a new mainstream in various countries through K-pop (Korean pop music), drama series, films etc. The success of Korean pop culture is proven by the emergence of the term